1994
DOI: 10.1007/bf02172283
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal classical eye-blink conditioning in autism

Abstract: Cerebellar and limbic system pathologies have been reported in persons with autism. Because these brain areas are involved centrally in the acquisition and performance in classical eye-blink conditioning, this study evaluated conditioning in 11 persons with autism. Compared to matched controls, persons with autism learned the task faster but performed short-latency, high-amplitude conditioned responses. In addition, differences in learning the extinction rates systematically varied with age thus suggesting a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
164
3
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(189 citation statements)
references
References 39 publications
20
164
3
2
Order By: Relevance
“…Significantly elevated levels of these neurotransmitters in the cerebellum could cause enhanced eye-blink learning in MAO A/B KO mice. Finally, we note a study of eye-blink conditioning in autistic children (52) in which it was reported that the autistic children learned this task faster than age-matched normal control children, just as is the case for our MAO A/B KO mice. Future studies are warranted to find out the neuroanatomical abnormalities in the cerebellum in MAO A/B KO mice.…”
Section: Mao A/b Ko Mice Showed Enhanced Contextual and Cue Memory Andsupporting
confidence: 53%
“…Significantly elevated levels of these neurotransmitters in the cerebellum could cause enhanced eye-blink learning in MAO A/B KO mice. Finally, we note a study of eye-blink conditioning in autistic children (52) in which it was reported that the autistic children learned this task faster than age-matched normal control children, just as is the case for our MAO A/B KO mice. Future studies are warranted to find out the neuroanatomical abnormalities in the cerebellum in MAO A/B KO mice.…”
Section: Mao A/b Ko Mice Showed Enhanced Contextual and Cue Memory Andsupporting
confidence: 53%
“…Among adolescents and young adults with autism (12-29 years old), an inverse correlation was found between caudate volume and ritualistic-repetitive behaviors (with and without total brain volume as a covariate), such as the presence of compulsions/rituals and difficulty changing routine (Sears et al 1994). In a somewhat older adult sample (17-55 years old) with an ASD diagnosis, a direct relationship between repetitive behaviors and right caudate volumes was noted (Hollander et al 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Analysis of caudate volume in adolescents and adults indicated no differences between individuals without psychiatric diagnoses and those diagnosed with autism when a measure of total brain was controlled (Gaffney et al 1989;Hardan et al 2003;Sears et al 1999). However, significantly larger caudate volumes were found in autistic samples when total brain volume was not included (Herbert et al 2003;Sears et al 1994). The latter study used data from children ages 7-11 years, and found that different brain structures may be disproportional in size, being excessively large or small, in young autistic boys.…”
Section: Introductionmentioning
confidence: 93%
“…[45][46][47][48] They also extend to the reciprocity/temporal synchrony skills required for conversation. [49][50][51][52] Objectively recorded atypical sleep architecture in young adults with high-functioning autism and Asperger syndrome 53 and in children with autistic disorder 54 shows association between sleep profiles and autistic symptomatology.…”
Section: Timing Difficulties and Autismmentioning
confidence: 99%